2016
DOI: 10.1111/rda.12702
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Boar Sperm with Nanoliposomes Prepared from Synthetic Phospholipids

Abstract: Liposomes are artificial membrane vesicles that can be used to test and model the functions and interactions of various biological membranes, or as a carrier system to deliver biologically active substances into the cells, or to incorporate lipids into the plasma membrane of target cells to modify membrane structure-function relationships. Sperm plasma membrane undergoes lipid modification during maturation in epididymis and during capacitation in the female reproductive tract to facilitate fertilization. Natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Lipids from different SM are subject to exchange and renewal by various mechanisms, such as endocytosis, exocytosis, contacts between different membranes and non-membrane lipid vesicles and by non-vesicular lipid carrier trafficking [ 15 , 16 ]. For example, the compositions of lipids in the SM have been shown to be susceptible to compositional changes by the incorporation/fusion of nanoliposomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipids from different SM are subject to exchange and renewal by various mechanisms, such as endocytosis, exocytosis, contacts between different membranes and non-membrane lipid vesicles and by non-vesicular lipid carrier trafficking [ 15 , 16 ]. For example, the compositions of lipids in the SM have been shown to be susceptible to compositional changes by the incorporation/fusion of nanoliposomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Garrett et al [ 28 ], using liposomes loaded with membrane-impermeable agents, reported that these vesicles interact with spermatozoa; in addition, when loaded with messengers, such as calcium ions, the liposomes were proposed as a useful tool for investigating the cell signaling linked to sperm activation. Many other literature papers have reported interactions between loaded liposomes and spermatozoa, which have simply analyzed the effect of the loaded compound [ 12 , 13 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tyrosine metabolism pathway have been suggested to play important roles in sperm capacitation, epididymal duct contractility and sperm quality (Cavariani et al ., ). The glycerophospholipid metabolism pathway may be important for maturation of sperm membrane and maintenance of membrane integrity of epididymal epithelial cells (Turner, ; Kasimanickam & Buhr, ).…”
Section: Discussionmentioning
confidence: 99%